The effects of two different types of dynamic warm-up and static stretching on power and speed - Christensen, B.; Napoli, R.; Hackney, K.; Miller, J.; Murata, H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Static stretching has often been found to decrease performance in power and speed activities, but dynamic warm-ups usually increase performance. We examined the effects of a mini-band warm-up, a medicine ball warm-up, and static stretching on 10m and 20m sprint times, as well as overhead medicine ball throw performance. Twenty-four Division I female soccer players completed the three warm-ups and a control 5 minute jog condition on separate days and were tested on the 10m and 20m sprint times and overhead medicine ball throw. ANOVA's and follow-up paired t-tests (p<0.05) were used to determine differences between the warm-ups. Significant differences were found between groups for the 1 Om sprint times but not for the 20m sprint times or the overhead medicine ball throw.